PERAN RENTENIR DALAM UPAYA MENYELESAIKAN MASALAH EKONOMI KELUARGA PEDAGANG PASAR AGUSSALIM PEKANBARU - ARDANI ARDANI; Almasdi Syahza; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstrakWorld trade is known as the world's public sector informal. For traders who have economic difficulties are very brave to do loans, one of which is a loan shark loan in Agussalim Market Pekanbaru. Research purpose to role of moneylenders in an effort to resolve the economic problems Agussalim Pekanbaru family of market traders, as well as the level of satisfaction of respondents to the moneylender loans. This sample in data were analyzed using descriptive methods, whereas respondents used to analyze the Likert scale. Respondents said moneylender loans act to help the economy, while the respondents through the ease of loans, as well as the system of installment each working day respondents. This is stated in the results of the analysis of respondents in the high category. With satisfaction of respondents to a loan shark loan in the satisfied category. At policy the moneylenders, punctuality, service, contributions and loan shark moneylenders. Thus, the role of credit loan by moneylenders in the market Agussalim can help solve economic problems family traders through good attitude given moneylenders for loans with fixed lending consequences of early repayment of the loan agreement up. Loans moneylenders operating in the market Agussalim can attract customers as loyal customers credit loan moneylenders.Keywords : Moneylenders Role, Customer Satisfaction